Features of the Functioning of Jus Cogens Norms in Time of Armed Aggression - Melnychenko, Vladyslav (Problems of legality, 2025)
The article is dedicated to the study of the legal nature of jus cogens norms. The relevance of the topic is stipulated by the need to ensure compliance with the general international law peremptory norms, which is a prerequisite for ensuring stable and reliable functioning of the international security system. The article emphasizes the special status of these norms. The purpose of the article is to identify and study the cases of functioning of general international law peremptory norms in a special regime. The achievement of this goal was made possible by applying a comprehensive approach which forms the methodological basis of the study. In the article a number of general scientific and special research methods are used, in particular: comparison, dialectical analysis and synthesis, comparative legal method, formal legal method, logical legal method. The author examines the features of certain jus cogens norms under the normal functioning of the international security system and in time of serious threats – in the context of an act of armed aggression. The author confirms that under the normal functioning of the international security system, compliance with jus cogens norms is an unconditional obligation of each State. It is established that within the framework of international law there are signs of the existence of a special regime in which certain jus cogens norms operate. It is found that when exercising the right to self-defence in the context of armed aggression, the protective effect of certain general international law peremptory norms against the aggressor State temporarily ceases to be effective, giving the affected State the right to legitimately use force and violate the territorial integrity of the aggressor, but only within the external aspect of the territorial integrity of the State – territorial inviolability. Furthermore, the author suggests that within the framework of exercising the right to self-defence, the victim has the right to take enforcement measures which formally contain signs of interference in the internal affairs of the aggressor. In addition, the author puts forward the idea that the existence of a special regime for the operation of certain peremptory norms of general international law is evidence of the possibility of its extension to legal relations of international legal responsibility, which outlines the prospects for further research.